Unlearning Some of our Social Scientist Habits - E. Jane Davidson (The Evaluation Center at Western Michigan University, 2007)
According to the organizational learning literature, some of the most important learning an organization can do is in the form of organizational unlearning-getting rid of erroneous or dysfunctional knowledge, habits, and practices. Simply adding new skills, behaviors, and ways of thinking isn't enough. Without some explicit attention to the process of unlearning, existing knowledge and know-how becomes a barrier to constructive change and new learning.